2022
DOI: 10.1155/2022/8005538
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Relationship between Unexplained Recurrent Abortion and HLA-DQ Gene Polymorphism

Abstract: Objective. The study aimed to investigate the relationship between human leukocyte antigen (HLA-DQB1) gene variants and recurrent miscarriage. Methods. HLA-DQ gene polymorphisms (PCR-SSP) were detected in 50 couples with recurrent miscarriage (URSA group) and 30 couples with normal births (control group) using sequence-specific primer-guided polymerase chain reaction. Results. The frequency of the DQB1 ∗ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…Consistent with our earlier finding on Lebanese women, no specific DQB1 alleles were found to be linked with RPL among Tunisian women 5 . This was in prominent contrast to Chinese, 52 Danish, 27 Kazakh, 40 and South Indian 25 studies, which described an association of DQB1*03 40,52 and DQB1*05 27,53 with altered risk of RPL. On the other hand, DPB1*01:01:01 was positively associated, while both DPB1*04:01:01 and DPB1*14:01:01 were negatively associated with RPL in our study cohort.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our earlier finding on Lebanese women, no specific DQB1 alleles were found to be linked with RPL among Tunisian women 5 . This was in prominent contrast to Chinese, 52 Danish, 27 Kazakh, 40 and South Indian 25 studies, which described an association of DQB1*03 40,52 and DQB1*05 27,53 with altered risk of RPL. On the other hand, DPB1*01:01:01 was positively associated, while both DPB1*04:01:01 and DPB1*14:01:01 were negatively associated with RPL in our study cohort.…”
Section: Discussionsupporting
confidence: 89%
“…As for FOXP3 -924 (A > G) and -6054 (del > ATT), those SNPs were not associated with immunological indices. Although -6054 (del > ATT) has been associated with other autoimmune diseases [ 30 ], the genetic mutations alone do not have much effect [ 33 ]. Since a combined analysis can better understand the role of FOXP3 variants in SLE, we studied the association of FOXP3 haplotype with immunological indices.…”
Section: Resultsmentioning
confidence: 99%
“…The Hardy–Weinberg equilibrium (HWE) was evaluated in the control group using Pearson’s Chi-square test, with an HWE analysis with a p value exceeding .05, suggesting that the population under study is representative [ 28 ]. Besides, the Chi-square test was employed to compare the distribution frequencies of genotypes and alleles, with a significance level set at p < .05 [ 29 ], aiming to evaluate the association between FOXP3 polymorphisms (-3279 C/A, -924 A/G and -6054 del/ATT) and SLE risk [ 30 ]. Furthermore, gender-based subgroup analysis was performed to investigate the potential gender-specific associations of FOXP3 polymorphisms with SLE susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%